The effect of a rocky terrain for CubeSat landing on asteroid surfaces. Issue 1 (1st January 2023) - Rusconi, Martina; Ferrari, Fabio; Topputo, Francesco
Abstract: The paper describes a general modelling procedure to build a simulation tool to investigate contact motion of a CubeSat on an asteroid surface. We investigate landing performance and landing success for the case of elastic rocky terrain and flat surfaces. As a case study, we focus on the disposal of ESA's Hera Milani CubeSat by landing on the moon of Didymos binary asteroid system. The simulation environment includes the modelling of real shape and 6-DOF motion of the lander, the shape-based gravity models of Didymos and Dimorphos and rocks on surface, that are generated as physical obstacles. Trends and estimates on the performance of the landing phase and the most relevant effects on the outcome of the soil interaction process, are inferred. The statistical results on settling time, dispersion area and motion characteristics, such as number of bounces, show and quantify the effect of rocks on a successful passive and permanent landing.